Switching of Current Rectification Ratios within a Single Nanocrystal by Facet-Resolved Electrical Wiring - Vogel, Yan; Zhang, Jinyang; Darwish, Nadim; Ciampi, Simone (American Chemical Society, 2018)
Here we show that within a single polyhedral metal oxide nanoparticle a nanometer-scale lateral or vertical sliding of a small metal top contact (e.g., <50 nm) leads to a 10-fold change in current rectification ratios. Electron tunnelling imaging and constant-force current-potential analysis in atomic force microscopy demonstrate that within an individual p-n rectifier (a Cu2O nanocrystal on silicon) the degree of current asymmetry can be modulated predictably by a set of geometric considerations. We demonstrate the concept of a single nanoscale entity displaying an in-built range of discrete electrical signatures and address fundamental questions in the direction of "landing" contacts in single-particle diodes. This concept is scalable to large 2D arrays, up to millimetres in size, with implications in the design and understanding of nanoparticle circuitry.